Alterations in PBP 1A Essential for High-Level Penicillin Resistance in Streptococcus pneumoniae - Smith, Anthony M. (American Society for Microbiology, 1998)
High-level penicillin resistance in pneumococci is due to alterations in penicillin-binding proteins (PBPs) 2X, 2B, and 1A. We have sequenced the penicillin-binding domain of PBP 1A from penicillin-resistant South African pneumococcal isolates and have identified amino acid substitutions which are common to all the resistant isolates analyzed. Site-directed mutagenesis was then used to determine whether particular amino acid substitutions at specific positions in PBP 1A mediate penicillin resistance. PCR was used to isolate PBP 2X, 2B, and 1A genes from clinical isolate 8303 (penicillin MIC, 4 μg/ml). These wild-type PBP genes were cloned into pGEM-3Zf and were used as the transforming DNA. Susceptible strain R6 (MIC, 0.015 μg/ml) was first transformed with PBP 2X and 2B DNA, resulting in PBP 2X/2B-R6 transformants for which MICs were 0.25 μg/ml. When further transformed with PBP 1A DNA, 2X/2B/1A-R6 transformants for which MICs were 1.5 μg/ml were obtained. Site-directed mutagenesis of the PBP 1A gene from isolate 8303 was then used to reverse particular amino acid substitutions, followed by transformation of PBP 2X/2B-R6 transformants with the mutagenized PBP 1A DNA. For PBP 2X/2B/1A-R6 transformants, the introduction of the reversal of Thr-371 by Ser or Ala in PBP 1A decreased the MIC from 1.5 to 0.5 μg/ml, whereas the reversal of four consecutive amino acid substitutions (Thr-574 by Asn, Ser-575 by Thr, Gln-576 by Gly, and Phe-577 by Tyr) decreased the MIC from 1.5 to 0.375 μg/ml. These data reveal that amino acid residue 371 and residues 574 to 577 of PBP 1A are important positions in PBP 1A with respect to the interaction with penicillin and the development of resistance.